2012
DOI: 10.1002/cm.21088
|View full text |Cite
|
Sign up to set email alerts
|

Microtubule modifications and stability are altered by cilia perturbation and in cystic kidney disease

Abstract: Summary Disruption of the primary cilium is associated with a growing number of human diseases collectively termed ciliopathies. Ciliopathies present with a broad range of clinical features consistent with the near ubiquitous nature of the organelle and its role in diverse signaling pathways throughout development and adult homeostasis. The clinical features associated with cilia dysfunction can include such phenotypes as polycystic kidneys, skeletal abnormalities, blindness, anosmia, and obesity. Although the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
31
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 43 publications
(35 citation statements)
references
References 28 publications
3
31
1
Order By: Relevance
“…However the findings agree with previous studies which show that HDAC6 is required for cilia disassembly in response to heat shock and that this inhibits hedgehog signalling 34 . While destabilisation of the axoneme might be influencing IFT and the traffic of Gli proteins through the cilium, previous studies have also linked ciliary dysfunction to changes in whole cell HDAC6 activity and tubulin acetylation levels 45 . While, gross changes in the level of whole cell tubulin acetylation were not observed in this study (not shown), subtle changes in the acetylation status of cytoplasmic microtubules could potentially affect cellular function by modulating kinesin motor activity and thus microtubule transport throughout the cell 46 .…”
Section: Discussionsupporting
confidence: 92%
“…However the findings agree with previous studies which show that HDAC6 is required for cilia disassembly in response to heat shock and that this inhibits hedgehog signalling 34 . While destabilisation of the axoneme might be influencing IFT and the traffic of Gli proteins through the cilium, previous studies have also linked ciliary dysfunction to changes in whole cell HDAC6 activity and tubulin acetylation levels 45 . While, gross changes in the level of whole cell tubulin acetylation were not observed in this study (not shown), subtle changes in the acetylation status of cytoplasmic microtubules could potentially affect cellular function by modulating kinesin motor activity and thus microtubule transport throughout the cell 46 .…”
Section: Discussionsupporting
confidence: 92%
“…Interestingly, we observed significantly fewer MTs in the leading edge of Ift88 depleted compared to non-induced control cells ( Fig 5E and 5F ). We wondered if MT stability was affected and assessed the amount of posttranslational modification in migrating Ift88 deficient cells [ 29 ]. This revealed no difference in the amount of acetylated Tubulin (data not shown) compared to control cells.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it was found that tubulin is hyperacetylated in a kidney cell line that lacks primary cilia due to the absence of Kif3a expression [54]. Impaired tubulin polyglutamylation causes cilia dysfunction which leads to primary ciliary dyskinesia [55] and affected development of the spermatid flagella in mice [56].…”
Section: Discussionmentioning
confidence: 99%